2021
DOI: 10.3390/ma14102647
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Application of Porous Tantalum and Its New Development for Bone Tissue Engineering

Abstract: Porous tantalum (Ta) is a promising biomaterial and has been applied in orthopedics and dentistry for nearly two decades. The high porosity and interconnected pore structure of porous Ta promise fine bone ingrowth and new bone formation within the inner space, which further guarantee rapid osteointegration and bone–implant stability in the long term. Porous Ta has high wettability and surface energy that can facilitate adherence, proliferation and mineralization of osteoblasts. Meanwhile, the low elastic modul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 213 publications
(289 reference statements)
0
32
0
1
Order By: Relevance
“…Porous tantalum is becoming more and more widely used in orthopedic implant surgery due to its excellent bone integration properties and elastic modulus matching with natural bone tissue. 37 Compared with the large amount of research on the surface modification of titanium, there are less literature reports about the modification of the porous tantalum scaffold. The chemical properties of tantalum are relatively inactive, 38 which brings challenges to give tantalum new biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Porous tantalum is becoming more and more widely used in orthopedic implant surgery due to its excellent bone integration properties and elastic modulus matching with natural bone tissue. 37 Compared with the large amount of research on the surface modification of titanium, there are less literature reports about the modification of the porous tantalum scaffold. The chemical properties of tantalum are relatively inactive, 38 which brings challenges to give tantalum new biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…This technique can solve the problem of bone absorption or transmission of diseases ( Issack, 2013 ; Divano et al, 2018 ). Porous tantalum material has been widely used in many fields of orthopedics because of its excellent biocompatibility, corrosion resistance, and mechanical properties, and the porous structure is conducive to inducing host bone ingrowth and bone adhesion and is the main material of customized metal cone produced by Zimmer ( Bencharit et al, 2014 ; Potter et al, 2016 ; Huang et al, 2021 ). Howard et al (2011) treated patients with bone defects after TKA revision.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere it was suggested that pores greater than 300 µm are essential for bone in-growth ( Roosa et al, 2010 ). Making a balance between mechanical and biological properties of porous tantalum by regulating a reasonable pore/pore ratio is a key difficulty for future research and development ( Huang et al, 2021 ). The maximum bending strength of porous tantalum is 110 MPa, which can provide sufficient physiological support for newborn bone tissue.…”
Section: Physicochemical Properties and Biological Performancementioning
confidence: 99%